Action research in science education – an analytical review of the literature. Issue 3 (27th May 2018) - Laudonia, Ivano; Mamlok-Naaman, Rachel; Abels, Simone; Eilks, Ingo
Abstract: Action research is suggested as a way to engage teachers in curriculum development and the betterment of teaching practices in schools based on educational research activities. As in other educational domains, action research in science education is employed with both aims to better understand and develop teaching practices and to contribute to teacher continuous professional development. A variety of methodological approaches using action research in science education exists, from more technical toward more emancipatory interpretations. The range of educational settings and goals for which action research is performed is also quite broad. The purpose of this analytical review of the international available literature is to provide an overview of the main aspects in applying action research in science education.